Exploring Global Trends in Waqf Law: Insights from a Bibliometric Study - Kuswardani Dyah Ayu Kusumaningrum; Al Milla Hamidah; Andri Nirwana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to map the development of waqf and legal studies indexed in the Scopus database in the period 2016-2025 with a bibliometric approach. The analysis was carried out to identify the main trends, patterns of collaboration between authors, distribution of publications based on institutional and country affiliations, and characteristics of journal sources that became publication media. The bibliometric method was applied by utilizing VOSviewer software for co-occurrence network visualization and Microsoft Excel for quantitative data processing and analysis. The results show that Indonesia (43.5%) and Malaysia (23.1%) are the countries with the highest research productivity in this field, with significant contributions from the United States (11.6%). The International Islamic University was recorded as the academic institution with the highest number of publications (15.4%), followed by Universiti Kebangsaan Malaysia and Universitas Padjajaran (13.5% each). From an individual perspective, publication patterns show a relatively even distribution, with 40% of researchers producing three publications and 60% of researchers producing two publications. Analysis of journal sources revealed that the three main journals served as publication platforms for 13.9% of the total articles analyzed. Temporal trends show a significant increase in research productivity, with the highest spike in 2024 (22 publications) and the most notable acceleration of research occurring in the period 2018-2021. These findings indicate significant developments in waqf studies, particularly in countries with predominantly Muslim populations, and point to a growing research ecosystem with a wider diversification of publication platform.